Oxygen adsorbates on the Si(111)4×1-In metallic atomic wire: Scanning tunneling microscopy and density-functional theory calculations - Oh, Deok Mahn; Wippermann, S.; Schmidt, Wolf Gero; Yeom, Han Woong (Physical Review B)

The atomic structure of ternary amorphous TixSi1−xO2hybrid oxides - Landmann, M; Köhler, T; Rauls, E; Frauenheim, T; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

Rashba splitting and relativistic energy shifts in In/Si(111) nanowires - Gerstmann, Uwe; Vollmers, N. J.; Lücke, A.; Babilon, M.; Schmidt, Wolf Gero (Physical Review B)

Unraveling theLiNbO3X-cut surface by atomic force microscopy and density functional theory - Sanna, S.; Schmidt, Wolf Gero; Rode, S.; Klassen, S.; Kühnle, A. (Physical Review B)

IntrinsicLiNbO3point defects from hybrid density functional calculations - Li, Yanlu; Schmidt, Wolf Gero; Sanna, S. (Physical Review B)

Formation of Hydroxyl Groups at Calcium-Silicate-Hydrate (C-S-H): Coexistence of Ca–OH and Si–OH on Wollastonite(001) - Sanna, Simone; Schmidt, Wolf Gero; Thissen, Peter (The Journal of Physical Chemistry C)

Temperature dependent LiNbO3(0001): Surface reconstruction and surface charge - Sanna, S.; Hölscher, R.; Schmidt, Wolf Gero (Applied Surface Science)

Adsorption of PTCDA on Terraces and at Steps Sites of the KCl(100) Surface - Guo, Q.; Paulheim, A.; Sokolowski, M.; Aldahhak, Hazem; Rauls, E.; Schmidt, Wolf Gero (The Journal of Physical Chemistry C)

Influence of Coulomb-induced band couplings on linear excitonic absorption spectra of semiconducting carbon nanotubes - Liu, Hong; Schumacher, Stefan; Meier, Torsten (Physical Review B)
Starting from the extended Su-Schrieffer-Heeger model, multiband semiconductor Bloch equations are formulated in momentum space and applied to the analysis of the linear optical response of semiconducting carbon nanotubes (SCNTs). This formalism includes the coupling of electron-hole pair excitations between different valence and conduction bands, originating from the electron-hole Coulomb attraction. The influence of these couplings, which are referred to as nondiagonal interband Coulomb interaction (NDI-CI), on the linear excitonic absorption spectra is investigated and discussed for light fields polarized parallel to the tube direction. The results show that the intervalley NDI-CI leads to a significant increase of the band gap and a decrease of the exciton binding energy that results in a blueshift of the lowest-frequency excitonic absorption peak. The strength of these effects depends on the symmetry of the SCNT. Furthermore, for zigzag SCNTs with higher symmetry other nonintervalley NDI-CI terms also affect the spectral positions of excitonic absorption peaks.

Formation and control of transverse patterns in a quantum fluid of microcavity polaritons - Lewandowski, P.; Ardizzone, V.; Tse, Y. C.; Kwong, N. H.; Luk, M. H.; Lücke, A.; Abbarchi, M.; Bloch, J.; Baudin, E.; Galopin, E.; Lemaître, A.; Leung, P. T.; et al. (Ultrafast Phenomena and Nanophotonics XVIII)

Optical spectrum, perceived color, refractive index, and non-adiabatic dynamics of the photochromic diarylethene CMTE - Wiebeler, Christian; Bader, Christina A.; Meier, Cedrik; Schumacher, Stefan (Phys. Chem. Chem. Phys.)

Polycyclic Aromatic Hydrocarbons Obtained by Lateral Core Extension of Mesogenic Perylenes: Absorption and Optoelectronic Properties - Vollbrecht, Joachim; Bock, Harald; Wiebeler, Christian; Schumacher, Stefan; Kitzerow, Heinz-Siegfried (Chemistry - A European Journal)

Optical Spectroscopy of Graphene Quantum Dots: The Case of C132 - Riesen, Hans; Wiebeler, Christian; Schumacher, Stefan (The Journal of Physical Chemistry A)

Quantum Yields and Reaction Times of Photochromic Diarylethenes: Nonadiabatic Ab Initio Molecular Dynamics for Normal- and Inverse-Type - Wiebeler, Christian; Schumacher, Stefan (The Journal of Physical Chemistry A)

Spin excitations in solids from many-body perturbation theory - Friedrich, Christoph; Şaşıoğlu, Ersoy; Müller, Mathias; Schindlmayr, Arno; Blügel, Stefan (First Principles Approaches to Spectroscopic Properties of Complex Materials)
Collective spin excitations form a fundamental class of excitations in magnetic materials. As their energy reaches down to only a few meV, they are present at all temperatures and substantially influence the properties of magnetic systems. To study the spin excitations in solids from first principles, we have developed a computational scheme based on many-body perturbation theory within the full-potential linearized augmented plane-wave (FLAPW) method. The main quantity of interest is the dynamical transverse spin susceptibility or magnetic response function, from which magnetic excitations, including single-particle spin-flip Stoner excitations and collective spin-wave modes as well as their lifetimes, can be obtained. In order to describe spin waves we include appropriate vertex corrections in the form of a multiple-scattering T matrix, which describes the coupling of electrons and holes with different spins. The electron–hole interaction incorporates the screening of the many-body system within the random-phase approximation. To reduce the numerical cost in evaluating the four-point T matrix, we exploit a transformation to maximally localized Wannier functions that takes advantage of the short spatial range of electronic correlation in the partially filled d or f orbitals of magnetic materials. The theory and the implementation are discussed in detail. In particular, we show how the magnetic response function can be evaluated for arbitrary k points. This enables the calculation of smooth dispersion curves, allowing one to study fine details in the k dependence of the spin-wave spectra. We also demonstrate how spatial and time-reversal symmetry can be exploited to accelerate substantially the computation of the four-point quantities. As an illustration, we present spin-wave spectra and dispersions for the elementary ferromagnet bcc Fe, B2-type tetragonal FeCo, and CrO2 calculated with our scheme. The results are in good agreement with available experimental data.

The GW approximation for the electronic self-energy - Schindlmayr, Arno (Many-Electron Approaches in Physics, Chemistry and Mathematics)
Many-body perturbation theory is a well-established ab initio electronic-structure method based on Green functions. Although computationally more demanding than density functional theory, it has the distinct advantage that the exact expressions for all relevant observables, including the ground-state total energy, in terms of the Green function are known explicitly. The most important application, however, lies in the calculation of excited states, whose energies correspond directly to the poles of the Green function in the complex frequency plane. The accuracy of results obtained within this framework is only limited by the choice of the exchange-correlation self-energy, which must still be approximated in actual implementations. In this respect, the GW approximation has proved highly successful for systems governed by the Coulomb interaction. It yields band structures of solids, including the band gaps of semiconductors, as well as atomic and molecular ionization energies in very good quantitative agreement with experimental photoemission data.

Theoretical investigation of the band structure of picene single crystals within the GW approximation - Yanagisawa, Susumu; Morikawa, Yoshitada; Schindlmayr, Arno (Japanese Journal of Applied Physics)
We investigate the band dispersion and related electronic properties of picene single crystals within the GW approximation for the electronic self-energy. The width of the upper highest occupied molecular orbital (HOMOu) band along the Γ–Y direction, corresponding to the b crystal axis in real space along which the molecules are stacked, is determined to be 0.60 eV and thus 0.11 eV larger than the value obtained from density-functional theory. As in our recent study of rubrene using the same methodology [S. Yanagisawa, Y. Morikawa, and A. Schindlmayr, Phys. Rev. B 88, 115438 (2013)], this increase in the bandwidth is due to the strong variation of the GW self-energy correction across the Brillouin zone, which in turn reflects the increasing hybridization of the HOMOu states of neighboring picene molecules from Γ to Y. In contrast, the width of the lower HOMO (HOMOl) band along Γ–Y remains almost unchanged, consistent with the fact that the HOMOl(Γ) and HOMOl(Y) states exhibit the same degree of hybridization, so that the nodal structure of the wave functions and the matrix elements of the self-energy correction are very similar.

Many-body perturbation theory: The GW approximation - Friedrich, Christoph; Schindlmayr, Arno (Computing Solids: Models, ab initio Methods and Supercomputing)

Bright squeezed-vacuum source with 11 spatial mode - Pérez, A. M.; Iskhakov, T. Sh.; Sharapova, Polina; Lemieux, S.; Tikhonova, O. V.; Chekhova, M. V.; Leuchs, G. (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

Sub-cycle control of terahertz high-harmonic generation by dynamical Bloch oscillations - Meier, Torsten; Schubert, O.; Hohenleutner, M.; Langer, F.; Urbanek, B.; Lange, C.; Huttner, U.; Golde, D.; Kira, M.; Koch, S. W.; Huber, R. (Nature Photonics)
Ultrafast charge transport in strongly biased semiconductors is at the heart of high-speed electronics, electro-optics and fundamental solid-state physics1,2,3,4,5,6,7,8,9,10,11,12,13. Intense light pulses in the terahertz spectral range have opened fascinating vistas14,15,16,17,18,19,20,21. Because terahertz photon energies are far below typical electronic interband resonances, a stable electromagnetic waveform may serve as a precisely adjustable bias5,11,17,19. Novel quantum phenomena have been anticipated for terahertz amplitudes, reaching atomic field strengths8,9,10. We exploit controlled (multi-)terahertz waveforms with peak fields of 72 MV cm−1 to drive coherent interband polarization combined with dynamical Bloch oscillations in semiconducting gallium selenide. These dynamics entail the emission of phase-stable high-harmonic transients, covering the entire terahertz-to-visible spectral domain between 0.1 and 675 THz. Quantum interference of different ionization paths of accelerated charge carriers is controlled via the waveform of the driving field and explained by a quantum theory of inter- and intraband dynamics. Our results pave the way towards all-coherent terahertz-rate electronics.